Maritimisation: definition, draft of an indicator and application to countries and territories of the South West Indian Ocean (1992-2015) - (:unkn) unknown (My University, 2021)
Several countries and international institutions are using the terms “blue growth” or “blue economy” to describe their sustainable development strategy in the maritime sector. In this presentation we detach ourselves from these terms, which remain very vague today, and prefer the term “maritimization”, an economic and geographical concept that can be defined as the increase and intensification of maritime activities (transports, resource exploitation, leisure activities, state actions at sea, illegal activities, etc.). This presentation presents the results and the application of a method to measure maritimization through a set of indicators. Three groups of countries are studied over the period 1992–2015. The first is composed of the islands of the Southwest Indian Ocean: Comoros, Madagascar, Mauritius, Mayotte, Reunion and Seychelles. The second group is composed of the East African countries: Kenya, Mozambique, South Africa and Tanzania. Finally, the third group consists of a selection of countries that are considered as major maritime powers: China, France, Japan, the United Kingdom and the United States. In general, maritimization has been more rapid in the Southwest Indian Ocean, although there are significant differences between islands and by activity.
Keywords: African Research